An Approach to balance Learning and Procrastination through a Strategic Model in the context of Higher Education - Biswal, Aparajita; Bhatt, Nirav; Lathigara, Amit (Journal of Engineering Education Transformations, 2025)
My own behaviour baffles me. For I find myself doing what I really hate, and not doing what I really want to do! ST PAUL The statement given by St. Paul regarding the frequently changing mindset of Humans is a perfect fit. Sometimes we as Humans face a lot of confusion in our minds about what to do and what not to do. Due to some reasons, we try to postpone things related to our work often which is known as Procrastination. There are Procrastination Models having dimensions Psychologic, Personal and Pedagogic in the academic scenario. The study in this paper focuses on two research questions which analyze the cause of academic procrastination and proposes a strategic model, along with the concept of Deadline, to overcome it. This work also focuses on the pedagogic dimension considering both student and teacher perspectives of learning and avoiding procrastination.